2022
DOI: 10.3390/biology11020220
|View full text |Cite
|
Sign up to set email alerts
|

Different Arbuscular Mycorrhizal Fungi Established by Two Inoculation Methods Improve Growth and Drought Resistance of Cinnamomum Migao Seedlings Differently

Abstract: Drought stress is one of the greatest obstacles affecting field crop productivity in arid and semi-arid regions, and its severity and frequency are expected to increase due to human-induced changes to the environment and climate. Drought has led to rocky desertification in Karst regions. Cinnamomum migao is a unique, fast-growing medicinal plant of Southwest China that only thrives in Karst regions. Arbuscular mycorrhizal fungi (AMF) symbiosis alleviates drought stress in plants; however, establishment and fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…boosted seedling development of Pinus tabulaeformis. Moreover, only a few previous reports are showing the induction of drought stress tolerance by endophytes in plants, such as Epichloë endophyte induced the drought tolerance in Festuca arundinacea and Lolium perenne [ 55 ], consortia of Penicillium Phaeosphaeria , Penicillium chrysogenum, Penicillium brevicompactum , Alternaria sp., and Eupenicillium osmophilum induced drought resistance in Colobanthus quitensis [ 56 ], the combination of fungal isolates SMCD 2206, 2210, and 2215 belonging to Ascomycota drought tolerance in wheat [ 57 ], an endophytic consortium induced drought tolerance in hybrid popular [ 58 ], arbuscular mycorrhiza protected the chicory ( Cichorium intybus L.) against drought stress [ 59 ], and Cinnamomum Migao seedlings [ 60 ]. In addition, [ 61 ] found that an endophytic fungus ( Talaromyces omanensis) enhanced the multiplicative, physiochemical, and anatomical traits of drought-stressed tomato plants.…”
Section: Discussionmentioning
confidence: 99%
“…boosted seedling development of Pinus tabulaeformis. Moreover, only a few previous reports are showing the induction of drought stress tolerance by endophytes in plants, such as Epichloë endophyte induced the drought tolerance in Festuca arundinacea and Lolium perenne [ 55 ], consortia of Penicillium Phaeosphaeria , Penicillium chrysogenum, Penicillium brevicompactum , Alternaria sp., and Eupenicillium osmophilum induced drought resistance in Colobanthus quitensis [ 56 ], the combination of fungal isolates SMCD 2206, 2210, and 2215 belonging to Ascomycota drought tolerance in wheat [ 57 ], an endophytic consortium induced drought tolerance in hybrid popular [ 58 ], arbuscular mycorrhiza protected the chicory ( Cichorium intybus L.) against drought stress [ 59 ], and Cinnamomum Migao seedlings [ 60 ]. In addition, [ 61 ] found that an endophytic fungus ( Talaromyces omanensis) enhanced the multiplicative, physiochemical, and anatomical traits of drought-stressed tomato plants.…”
Section: Discussionmentioning
confidence: 99%
“…Langeroodi et al (2020) reported the arbuscular mycorrhiza that protected the chicory (C. intybus L.) against water deficit and resulted in reduced photosynthetic efficiency. Different arbuscular mycorrhizal fungi have been reported to improve the growth and drought tolerance of C. Migao seedlings (Xiao et al, 2022). Halo et al (2020) found that an endophytic fungus (T. omanensis) enhanced the physiological, biochemical, and anatomical characteristics of tomato plants under drought stress.…”
Section: Discussionmentioning
confidence: 99%
“…(2020) reported the arbuscular mycorrhiza that protected the chicory ( C. intybus L.) against water deficit and resulted in reduced photosynthetic efficiency. Different arbuscular mycorrhizal fungi have been reported to improve the growth and drought tolerance of C. Migao seedlings ( Xiao et al., 2022 ). Halo et al.…”
Section: Discussionmentioning
confidence: 99%
“…Borkh.) [ 34 ], common marigold ( Calendula officinalis L.) [ 35 ], and woody plant ( Cinnamomum migao ) [ 36 ]. AMF have also been used to mitigate climate change effects, such as drought and salinity.…”
Section: Introductionmentioning
confidence: 99%